ANALISIS PENGARUH CUSTOMER SERVICE EXPERIENCE TERHADAP BEHAVIOR INTENTIONS - Syahid, Kendid (2014)
Accommodation industry such as hotel is an industry that has an important role in tourism. As in the case of Indonesia's tourism industry continues to progress, especially hotel accommodation services business growing rapidly as well. Hotels are accommodation support a growing tourism activities in Indonesia. One of the provinces that have rapid progress in the hospitality industry is Yogyakarta. Yogyakarta is one of the provinces that attracted many tourists both domestic and foreign for a vacation, business activities and other purposes. One hotel located in Yogyakarta is Sheraton Mustika Yogyakarta Resort and Spa. Sheraton Mustika Yogyakarta is a city resort themed hotel that could accommodate the needs of the guest's stay as a vacation, business, conferences and other necessities to luxury 5 star resort facilities. By 2013, Sheraton Mustika Yogyakarta' individual guest behaves decreased intention to stay longer, recommending Sheraton Mustika Yogyakarta and repurchasing intention. Those are in marketing theory referred to behavior intentions. Therefore, management of Sheraton Mustika Yogyakarta pursuing a strategy named Star Customer Experience in marketing theory called the customer service experience. This research aims to describe the customer service experience, decribe of behavior intentions and the influence of customer service experience towards behavior intentions. The population in this research is the first timer individual guests staying at Sheraton Mustika Yogyakarta. The independent variable in this study is the customer service experience (X) and behavior intentions (Y) as the dependent variable. The method used is descriptive and verificative research method. This research is done in less than one year or a cross-sectional method. The sampling technique used is systematic random sampling with data analysis techniques using multiple regression analysis. The results showed the highest valuation for customer service experience (X) is empathy, whereas for the lowest valuation is recognition. The highest guest valuation for behavior intentions is repurchasing intention and willingness to recommend as the lowest valuation. Simultaneous, customer service experience significantly influence behavior intentions.